2021
DOI: 10.1109/access.2021.3109269
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Engineering Based on Reinforcement Learning for Service Function Chaining With Delay Guarantee

Abstract: Network Function Virtualization (NFV) is an approach that provides a network service provider with agility and cost-efficiency in managing 6G network services. Standard traffic engineering rules are known limited in assuring a very stringent delay requirement in NFV when a traffic flow is required to follow a sequence of network functions scattered in data center networks. This paper proposes an innovative model and algorithm of traffic engineering for service function chaining (SFC) to maximize cost-efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Our future work will address the dynamics of service demand parameters and various performance metrics as in [6,23]. We also can consider a more general coordination model or the federation of IoT providers for enhancing service quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our future work will address the dynamics of service demand parameters and various performance metrics as in [6,23]. We also can consider a more general coordination model or the federation of IoT providers for enhancing service quality.…”
Section: Discussionmentioning
confidence: 99%
“…After RSS obtains a new feasible solution, RSS replaces the current solution with the neighborhood solution if the neighborhood solution is better than the current solution (i.e., lines [19][20][21][22][23][24]. Otherwise, to overcome local optimization, RSS probabilistically switches the current solution to the neighborhood solution (i.e., lines 25-30).…”
Section: Simulated Annealing-based Approximation Algorithm For Rsmentioning
confidence: 99%
“…In the traffic engineering framework, the study of [27] demonstrated the capability to locate the optimal placement of VNF to determine highly efficient service function chaining (SFC) in a network function virtualization (NFV) environment using MILP and approximation solution. The findings from [27] indicate the optimum method to address strict SFC routing policy, the efficient management of VNF usability, and the identification of an algorithm that works efficiently in specific scenarios. The study in [28] demonstrated deep reinforcement learning (DRL), a subsection in machine learning frameworks.…”
Section: Related Workmentioning
confidence: 99%
“…Gatekeeper [30] is an example of a rate-limit approach, where Linux hierarchical token buckets are used to enforce rate limits. SENIC [31] uses hardware-assisted rate limits at traffic sources to improve performance of latency-sensitive applications. Along the same lines, Silo [32] dynamically enforces rate limits on virtual machines in order to achieve performance guarantees.…”
Section: Related Workmentioning
confidence: 99%